2005
DOI: 10.1007/s11178-005-0211-1
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization of 2-Thioxo-1,2,3,4-tetrahydropyrimidin-4-ones with Oxiranes and 2-Haloacetonitriles

Abstract: A procedure was developed for the synthesis of tetrahydropyrimidine-2,4-diones by desulfurization of 2-thioxo-1,2,3,4-tetrahydropyrimidin-4-ones with oxiranes or 2-haloacetonitriles in polar solvents in the presence of a base.It is known that 2-thioxo-1,2,3,4-tetrahydropyrimidin-4-one derivatives differently react with different alkylating agents. In most cases, the reaction gives the corresponding 2-alkylsulfanylpyrimidin-6(1H)-ones or 2-alkylsulfanyl-1-alkylpyrimidin-4(1H)-ones, while 2-chloroacetic acid rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…It was demonstrated that this reaction is pH‐dependent, the main product formed at pH 6.6 being pirimidinone riboside (H 2 U), whereas at pH 7.6, uridine is formed. Correspondingly, in case of 2‐thiouracil, the nucleophilic substitution of sulfur by oxygen takes place after the alkylation of the thiol group with 2‐haloacetonitryles or oxirane (Novakov et al ., ). For the desulfuration in which DUF523 proteins are involved, the scenario is yet unclear.…”
Section: Resultsmentioning
confidence: 97%
“…It was demonstrated that this reaction is pH‐dependent, the main product formed at pH 6.6 being pirimidinone riboside (H 2 U), whereas at pH 7.6, uridine is formed. Correspondingly, in case of 2‐thiouracil, the nucleophilic substitution of sulfur by oxygen takes place after the alkylation of the thiol group with 2‐haloacetonitryles or oxirane (Novakov et al ., ). For the desulfuration in which DUF523 proteins are involved, the scenario is yet unclear.…”
Section: Resultsmentioning
confidence: 97%
“…The intermediates i were decarboxylated in strong acidic medium to afford 6‐arylpyrimidine‐2,4‐diols ii which are the enol forms of compounds 5a , 5b , 5c , 5d , 5e , 5f , 5g , 5h (Scheme ). Compounds 5a,b,f have previously been prepared through desulfurization of the corresponding 2‐thiouracil derivatives [14–16]. Compounds 5a , 5b , 5c , 5d were brominated with N ‐bromosuccinimide in absolute ethanol in the presence of benzoyl peroxide at room temperature to give the 5‐bromouracil derivatives 6a , 6b , 6c , 6d (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…5‐Bromo‐6‐arylmethyluracils were used as inhibitors of thymidine phosphorylase [11–13]. Uracil derivatives are known to be synthesized by refluxing the corresponding thiouracils with 10% aqueous chloroacetic acid [14–21]. Thiouracils are synthesized by the condensation of the appropriate β‐ketoester with thiourea in strong basic medium [14–21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available materials were used without further purifications. 6-Methyluracil was produced by the oxidation of 6-methylthiouracil by 1,2propyleneoxide [15].…”
Section: Methodsmentioning
confidence: 99%